2022
DOI: 10.20473/juxta.v13i12022.6-8
|View full text |Cite
|
Sign up to set email alerts
|

Early- and Late-Onset Preeclampsia at a Tertiary Hospital in 2016

Abstract: Introduction: Preeclampsia is still one of the major causes of maternal morbidity and mortality worldwide. Preeclampsia nowadays has another classification, early-onset preeclampsia and late-onset preeclampsia. This study aimed to evaluate the differences between early-onset and late-onset preeclampsia in Dr. Soetomo General Hospital, Surabaya in 2016.Methods: This was an analytic observational study, evaluating the difference between early- and late-onset preeclampsia in terms of maternal data, medical histor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 9 publications
(15 reference statements)
0
1
0
Order By: Relevance
“…This result is in line with the findings of Anindya et al (2022) in a study at the Madiun public hospital, Indonesia found that most mothers with preeclampsia were multigravidas (145 out of 216 or 67%)33 ke 18. Kinanti (2022), in the study of hypertension in pregnant women at a tertiary hospital in Surabaya, Indonesia, found that multigravidas experience more late-onset preeclampsia (85.4%) than primigravidas (35.6%) and early-onset preeclampsia occurs mainly in nulliparous women and primigravida (24).…”
Section: Discussionmentioning
confidence: 99%
“…This result is in line with the findings of Anindya et al (2022) in a study at the Madiun public hospital, Indonesia found that most mothers with preeclampsia were multigravidas (145 out of 216 or 67%)33 ke 18. Kinanti (2022), in the study of hypertension in pregnant women at a tertiary hospital in Surabaya, Indonesia, found that multigravidas experience more late-onset preeclampsia (85.4%) than primigravidas (35.6%) and early-onset preeclampsia occurs mainly in nulliparous women and primigravida (24).…”
Section: Discussionmentioning
confidence: 99%